Personal protective equipment for reducing the risk of COVID-19 infection among healthcare workers involved in emergency trauma surgery during the pandemic: An umbrella review protocol (2021)
Introduction Many healthcare facilities in low-income and middle-income countries are inadequately resourced and may lack optimal organisation and governance, especially concerning surgical health systems. COVID-19 has the potential to decimate these already strained surgical healthcare services unless health systems take stringent measures to protect healthcare workers (HCWs) from viral exposure and ensure the continuity of specialised care for patients. The objective of this broad evidence synthesis is to identify and summarise the available literature regarding the efficacy of different personal protective equipment (PPE) in reducing the risk of COVID-19 infection in health personnel caring for patients undergoing trauma surgery in low-resource environments. Methods We will conduct several searches in the L·OVE (Living OVerview of Evidence) platform for COVID-19, a system that performs automated regular searches in PubMed, Embase, Cochrane Central Register of Controlled Trials and over 30 other sources. The search results will be presented according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram. This review will preferentially consider systematic reviews of experimental and quasi-experimental studies, as well as individual studies of such designs, evaluating the effect of different PPE on the risk of COVID-19 infection in HCWs involved in emergency trauma surgery. Critical appraisal of eligible studies for methodological quality will be conducted. Data will be extracted using the standardised data extraction tool in Covidence. Studies will, when possible, be pooled in a statistical meta-analysis using JBI SUMARI. The Grading of Recommendations, Assessment, Development and Evaluation approach for grading the certainty of evidence will be followed and a summary of findings will be created. Ethics and dissemination Ethical approval is not required for this review. The plan for issemination is to publish review findings in a peer-reviewed journal and present findings at high-level conferences that engage the most pertinent stakeholders.